2008
DOI: 10.2147/opth.s2561
|View full text |Cite
|
Sign up to set email alerts
|

Potential bias in ophthalmic pharmaceutical clinical trials

Abstract: To make clinicians aware of potential sources of error in ophthalmic pharmaceutical clinical trials that can lead to erroneous interpretation of results, a critical review of the study design of various pharmaceutical ophthalmic clinical trials was completed. Discrepancies as a result of study shortcomings may explain observed differences between reported ophthalmic trial data and observed clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…On the other hand, Howard and colleagues found that industry‐funded neurology studies were more likely to have improperly registered their RCT in favour of statistically significant results (Howard et al. ), and Varner discussed extensively about potential bias in the field of ophthalmology (Varner ). When Alasbali et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, Howard and colleagues found that industry‐funded neurology studies were more likely to have improperly registered their RCT in favour of statistically significant results (Howard et al. ), and Varner discussed extensively about potential bias in the field of ophthalmology (Varner ). When Alasbali et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although industry support can help to improve study quality (Brown et al. ) and to offset the staggering costs of drug development and pharmaceutical trials (Varner ), this potentiates industry‐influenced reporting bias given possible conflict of interest (Chiu et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using publications with a high citation index and a practical orientation, as well as checking the accuracy of information related to the physicians’ workplace, hospital conditions, and patient group may help prevent these logical fallacies. 21 , 22 , 23 , 24 , 25 …”
Section: Logic and Fallaciesmentioning
confidence: 99%